2010
DOI: 10.1017/s0007114510000346
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin, the active phenolic component in kiwifruit, prevents hydrogen peroxide-induced inhibition of gap-junction intercellular communication

Abstract: We evaluated the effects of the two main kiwifruit cultivars (gold kiwifruit (GOK) and green kiwifruit (GRK)) and their active phenolic compound, quercetin, on H 2 O 2 -induced inhibition of gap-junction intercellular communication (GJIC) in WB-F344 rat liver epithelial cells. We found that both GOK and GRK protect WB-F344 cells from H 2 O 2 -induced inhibition of GJIC. The extracellular signal-regulated protein kinase 1/2 (ERK1/2) -connexin 43 (Cx43) signalling pathway is crucial for the regulation of GJIC, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 37 publications
3
22
0
Order By: Relevance
“…The obtained results of kiwi fruit bioactivity correspond with the reported data of Mikulic-Petkovsek, Schmitzer, Slatnar, Stampar, and Veberic (2012); NunesDamaceno, Muñoz-Ferreiro, Romero-Rodríguez, and Vázquez-Odériz (2013); and Pranamornkith et al (2012). Our results in vitro were similar to Lee et al (2010), where the effects of the two main kiwi fruit cultivars (gold and green kiwi fruits) and their active phenolic compounds were evaluated.…”
Section: Total Soluble Phenolssupporting
confidence: 90%
“…The obtained results of kiwi fruit bioactivity correspond with the reported data of Mikulic-Petkovsek, Schmitzer, Slatnar, Stampar, and Veberic (2012); NunesDamaceno, Muñoz-Ferreiro, Romero-Rodríguez, and Vázquez-Odériz (2013); and Pranamornkith et al (2012). Our results in vitro were similar to Lee et al (2010), where the effects of the two main kiwi fruit cultivars (gold and green kiwi fruits) and their active phenolic compounds were evaluated.…”
Section: Total Soluble Phenolssupporting
confidence: 90%
“…From the set of CPAs evaluated in this study, attenuation of GJIC inhibition induced by hydrogen peroxide or TPA has been reported only for quercetin (16, 31, 32), indole-3-carbinol (33), and curcumin derivates (34), whereas curcumin did not prevent TPA-induced inhibition of GJIC (35). Quercetin was also found to prevent inhibition of GJIC induced by DDT (16), but the ability of these CPAs to attenuate the effects of other GJIC inhibitors represent a novel finding of this study.…”
Section: Discussionmentioning
confidence: 94%
“…Antioxidative activity has been implicated as the principal mechanism responsible for prevention of hydrogen peroxide-dependent inhibition of GJIC by different CPAs (31, 3941). Such activity could explain also the observed attenuation of lindane-induced inhibition of GJIC in this study, since all investigated CPAs have been associated with antioxidative activity and with reduction of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, quercetin, the active phenolic component in kiwifruit, mediated by its free radical-scavenging activity, prevented hydrogen peroxideinduced inhibition of gap-junction intercellular communication in rat liver epithelial cells that is required for cell-cell communication in order to maintain homeostasis by facilitating direct exchanges of essential cellular metabolites and messengers less than 1-2 kDa (e.g. , cyclic AMP and ATP) [165][166][167]. Additionally, quercetin possesses chemopreventive activity against azoxymethane-induced colonic tumorigenesis in mice and pre-neoplastic lesions in rat hepatocarcinogenesis [167].…”
Section: Phenols and Phenolic Acidsmentioning
confidence: 99%